LONG-TERM EFFECTS OF OMEGA-3 POLYUNSATURATED FATTY ACIDS ON THE COURSE OF ISCHEMIC HEART DISEASE IN PATIENTS AFTER ST-ELEVATION MYOCARDIAL INFARCTION AT THE BACKGROUND OF MULTIPLE-VESSEL LESION CORONARY ATHEROSCLEROSIS - M. N. Sin’kova; T. V. Pepelyaeva; L. K. Isakov; N. I. Tarasov; A. T. Teplyakov (Кардиоваскулярная терапия и профилактика)
Currently there is enough evidence for that the use of omega-3-faty acids compounds in ischemic heart disease is followed by the decrease of mortality, and the efficacy of this usage in multivessel coronary lesions after primary percutaneous intervention (PCI) has not been studied.Aim. To evaluate the efficacy of long-term intake of the omega-3-polyunsaturated fatty acids compounds on the course of ischemic heart disease at the background of multiple coronary lesion after primary PCI.Material and methods. Totally 101 patient included at the age of 35-70 y.o., who had underwent primary PCI for the myocardial infarction with ST elevation and multiple vessel lesion of coronary arteries. The patients were selected into 2 groups: 1 group (n=68) — conservative tactics with the standard pharmacotherapy; 2nd group (n=33) — Omacor was added to the standard therapy.Results. In 36 months of follow-up in the Omacor group there was significant decrease of repeated myocardial infarctions, decompensating heart failure, angina progression and rhythm disorders. In 2nd group patients during the 36-month follow-up a better antiischemic effect achieved with 80,9% decrease of angina from the baseline (p<0,047) and by 27,6% of the heart failure severity. The increase of exercise tolerance by the 6-minute walking test during 36 months was the highest in the 2nd group — by 65%.Conclusion. Long-term prescription of omega-3-polyunsaturated fatty acids in ST elevation myocardial infarction with multiple vessel coronary lesions after primary PCI leads to the improvement of clinical condition, which then leads to the increase of exercise tolerance and better life quality.